2022
DOI: 10.1002/bab.2323
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of zerovalent iron nanoparticles for catalytic reduction of 4‐nitrophenol and decoloration of textile dyes

Abstract: We demonstrate a green chemistry approach to synthesize narrow-sized zerovalent iron (nZVI) nanoparticles using Artocarpus heterophyllus Lam. leaf extract as reducing and capping agent. The produced nZVI was characterized by various instrumental methods including ultraviolet-visible spectra, transmission electron microscopy, vibrating sample magnetometer (VSM), X-ray diffraction, and Fourier transform infrared spectroscopy. Based on the electron microscopy observations, the particle size was estimated to be ∼3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Presently, scientists are trying to degrade p-nitrophenol by exploiting the catalytic activity of various nanoparticles. It has been reported that iron nanoparticles synthesized by Jatropha [ 33 ] and Artocarpus heterophyllus [ 34 ] leaf extracts showed potential catalytic activity to degrade nitrophenol. It was also reported that iron oxides are capable of degrading nitrophenol in the presence of oxalate [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, scientists are trying to degrade p-nitrophenol by exploiting the catalytic activity of various nanoparticles. It has been reported that iron nanoparticles synthesized by Jatropha [ 33 ] and Artocarpus heterophyllus [ 34 ] leaf extracts showed potential catalytic activity to degrade nitrophenol. It was also reported that iron oxides are capable of degrading nitrophenol in the presence of oxalate [ 35 ].…”
Section: Introductionmentioning
confidence: 99%